PERILAKU STICKY COST TERHADAP BIAYA TENAGA KERJA DAN BEBAN USAHA PADA AKTIVITAS PENJUALAN - Rahmawati Kartikasari; Leny Suzan; Muhamad Muslih (JRAK, 2018)
This research aims to find the indication of sticky cost behavior in agricultural companies listed on Indonesian Stock Exchange in 2012-2015. Sticky cost is a cost that has no comparable character with changes in activity. These costs become sticky when the declining of company’s activity happens. This study used 9 companies as samples. The sampling technique used is purposive sampling. The analysis method used is multiple linear regression. It is found that the labor cost increased by 0,913 percent and operating expenses increrased by 0,146 percent when sales increased by 1 percent. In the other hand, when sales decreased by 1 percent, the labor cost decreased by 0,225 percent and operating expenses decreased by 0,131 percent. The result shows that there is indication of sticky cost behavior in the labor cost and operating expenses.